digital herbary of medicinal plants in the Adrián Moncada community territory (Revista Electrónica REDINE, 2019)
After approximately six months of work in the town of Río Claro, through this work, a significant experience is offered with a group of people from the Commune  Agroecological and Ecotourism Commander Adrian Moncada. This experience represents an alternative for other people in the face of the problem of access to medicines and the constant search for alternatives for Living Well. Participating Action Research is the method for approaching the study and the techniques used are the photographic record, debate, exhibition, systematization. So far there are evidences that allow the creation of a digital herbarium from plants that grow wild in the courtyards of houses, used to heal certain ailments and applied in everyday life, with a significant impact on the family, improving health, family budget and the protection of ancestral knowledge that reach today through orality. Among the conclusions of the study emerge the feasibility of creating a virtual herbarium that allows access to information without any limitation, thus forming a space for learning and study, as well as an important paradigm change to Life in this group of people.